The association of shift work and coronary heart disease risk factors among male factory workers in Kota Bharu, Kelantan - Mohd Nazri S.,; Tengku M. A,; Winn T.,; Choudhury S.R., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Shift work is one of the work hour systems in which a relay of employees extends the period of production beyond the conventional 8-hour working day. It has been found to be associated with various health problems and there is concern that shift workers are at higher risk to develop risk factors for coronary heart disease (CHD). The study was undertaken to examine relationships between shift work and CHD risk factors, namely hypertension, dyslipidaemia (either hypercholesterolaemia, hyper-low density lipoprotein-cholesterolaemia, hypo-high density lipoprotein-cholesterolaemia or hypertriglyceridaemia), high body mass index (BMI), hyperglycemia and physical inactivity among male factory workers in a factory in Kota Bharu, Kelantan. METHODS: This study was a contrived cross-sectional study of 76 shift and 72 day workers from one ofthe factories in Kota Bharu, Kelantan. Data was collected through a questionnaire on psychosocial and life-style factors, anthropometric and blood pressure measurement, fasting blood sugar and fasting lipid proJiles analyses. RESULTS: The prevalence of hypertension, hypercholesterolaemia, hypertriglyceridaemia and high body mass index (BMO were significantly higher among shift workers compared to day workers. There was no difference in the prevalence of hyperg[ycemia, hypo-high-density lipoprotein-cholesterolaemia, hyper-high-density lipoprotein-cholesterolaemia and physical inactivity. When the shiji workers were compared with the day workers, the aajusted odds ratio (OR) for hypertension, high BMI andphysical inactivity were 9.1 (95% CI 1.4-56.8), 2.9 (95% CI 1.3-6.1) and 7.7 (95% CI 2.1-27.5) respectively. There was neither association of shift work with dyslipidaemia, nor with hyperglycemia. CONCLUSIONS: There were positive association between shiji work and hypertension, high BMI andphysical inactivity which denotes a higher risk of CHD risk factors among shift workers compared to day workers.